Taxonomic review and microbial ecology in bacterial nanocellulose fermentation - Dourado, Fernando (2016)
Acetic acid bacteria (AAB) have a long history of use in several fermentation processes. Their exploitation gradually emerged in biotechnologic applications, especially in the biosynthesis of useful chemicals and processes for the manufacture of several fermented food products. Taxonomic studies, from traditional to polyphasic approaches, have gradually allowed the proper classification of several ABB into distinct genera and species, among them, the bacterial nanocellulose (BNC) producers, notably Komagataeibacter xylinus. Despite the advantages in using specific (isolated) strains for biotechnologic processes toward controlling the kinetics and process yield, mixed culture fermentations may provide an interesting approach to tailoring the properties of BNC and to increase the product yield when aiming at industrial scale. Microbial population dynamics may play a synergistic role in the coordinative substrate consumption and metabolites production, especially if using complex media (as is the case with low cost substrates, eg, residues from other processes). This chapter will first review the main historic steps involved in the taxonomic classification of AAB. It will then address the lying potential behind mixed microbial fermentations, from kombucha to nata de coco, both sharing in common, the contribution of cellulose-producing bacteria for the fermentation process.